ANALISIS KONDISI FISIK PADA PESERTA EKSTRAKURIKULER FUTSAL SMP NEGERI 9 BANJARBARU - Fahreza, Ilham; Akbar Fauzan, Lazuardy; Rahmadi (UNIB Press, 2025)
This study aims to analyze the physical condition of students participating in futsal extracurricular activities at State Junior High School 9 Banjarbaru. Physical condition is an important aspect in futsal because it directly affects the performance, endurance, speed, agility, and strength of players on the field. This study uses a quantitative descriptive approach with 21 students who actively participate in futsal extracurricular activities at the school. To measure the physical condition of the players, a series of standardized test instruments are used. The tests include muscle strength tests using hand dynamometer, back dynamometer, and leg dynamometer, muscle endurance tests using sit-ups, push-ups, and squat jumps; speed tests using a 30-meter run; agility tests using a beam side step, flexibility with a flexometer, and general endurance tests using a bleep test. The results show that most players are still in the category of lacking in some aspects of physical fitness, particularly in terms of muscle strength, speed, and agility. This study comprehensively evaluates all components of the main physical condition of futsal players of State Junior High School age and observes specific physical weaknesses in the futsal extracurricular population of State Junior High School. This research is an initial reference in the preparation of physical exercise programs to be more directed, which has not been carried out systematically in the formal education environment at the State Junior High School level, especially in Banjarbaru. With the improvement of a structured training program and according to needs, it is hoped that the physical condition of students can improve so that the performance and achievements of the futsal team of the State Junior High School 9 Banjarbaru will also increase.